COMMUNICATION ORGANIZATIONAL PATTERNS TO REGIONAL DISASTER MITIGATION AFTER THE COVID-19 PANDEMIC - Adhrianti, Lisa; Ayyash, Muhammad Yahya; Alfarabi, Alfarabi; Warsah, Idi; Firmansyah, Mas Agus (Interaksi: Jurnal Ilmu Komunikasi, 2024)
The COVID-19 pandemic, classified as a social disaster, continues to present challenges even in the post-pandemic era, especially in regions where public awareness and belief in the existence of COVID-19 remain low. This study focuses on identifying and analyzing the communication patterns employed by the Regional Disaster Management Agency (RDMA) of North Bengkulu Regency, Bengkulu Province, in mitigating the impact of the pandemic. The research aims to determine the organizational communication patterns within RDMA post-COVID-19 pandemic. A qualitative descriptive method was applied to explore the types and effectiveness of communication patterns—vertical, horizontal, and diagonal—used within the organization. The findings reveal that RDMA adopts a "wheel communication pattern" to coordinate disaster mitigation efforts, emphasizing the strategic use of digital platforms such as WhatsApp groups for instructions, reporting, and coordination among team members. This study provides insights into effective organizational communication strategies for regional disaster management and offers recommendations for future research to explore disaster mitigation efforts through digital communication channels and social media dissemination